Impact of cognitive impairment on heart failure prognosis: insights into central nervous system mechanism - Zhiyong Shi; Mingkai Yun; Binbin Nie; Enjun Zhu; Wei Fu; Baoci Shan; Sijin Li; Xiaoli Zhang; Xiang Li (EJNMMI Research)
Abstract Background Epidemiological studies have indicated that patients with heart failure (HF) who experience cognitive impairment (CI) have a poor prognosis. While poor self-management and compliance are suggested as contributing factors, they do not fully explain the underlying mechanisms of high risk of cardiac events in HF patients with CI. Given the interconnectedness of CI and the autonomic nervous system (ANS), both regulated by the central nervous system, this study investigated the relationship among cognitive function, metabolism in ANS-related brain regions, and major arrhythmic events (MAEs) in patients with HF with reduced ejection fraction (HFrEF). Results We retrospectively enrolled 72 patients with HFrEF who underwent gated myocardial perfusion imaging, heart and brain 18F-FDG positron emission tomography/computed tomography imaging, and cognitive testing. Cognitive function was evaluated using the Mini-Mental State Examination. During the follow-up period, 13 patients (17.8%) experienced MAEs. Patients with MAEs exhibited decreased cognitive function across various domains, including orientation, registration, and language and praxis (all p < 0.05). Patients with CI displayed a prolonged heart rate-corrected QT (QTc) interval and hypometabolism in the left hippocampus and bilateral caudate nuclei (all p < 0.05). Significant correlations were observed between cognitive function, QTc interval, and metabolism in ANS-related brain regions (all p < 0.05). Cox regression model analysis showed that the predictive value of cognitive function is not independent of the QTc interval and there is a significant interaction. The mediation analyses suggested that a prolonged QTc interval resulting from ANS disorder increased risk of MAEs in HFrEF patients with CI. Patients with CI exhibited reduced central autonomic network (CAN) connectivity. Conclusion ANS dysfunction, exacerbated by reduced metabolism in ANS-related brain regions and CAN connectivity, contributed to an increased risk of MAEs in HFrEF patients with CI. Graphical abstract